In vitro antibacterial activity of Moringa oleifera leaf and seed extracts against antibiotic-resistant bacteria and clinical isolates - Sakyibea Apenteng-Takyiako; Cecilia Afua Amoah Takyi; Mary Anti Chama; Mary-Magdalene Osei; Eric Sampane Donkor; Godfred Futagbi (BMC Complementary Medicine and Therapies)
Abstract Background Resistance to antibiotic has increased extensively over the years, posing a serious threat to public health. Plants are promising sources of antibiotic-resistance inhibitors. The aim of this study is to investigate the antibacterial properties leaf and seed extracts of Moringa oleifera against strains of pathogenic bacteria. Methods Eight extracts of M. oleifera leaves and seeds were prepared using four solvents; water, ethanol, ethyl acetate and petroleum ether, and evaluated against drug-resistant clinical isolates and standard laboratory strains of Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa using disc diffusion method. Minimum inhibitory concentration of the extracts was determined by broth microdilution method. Results The results show that aqueous extracts of both leaves and seeds had higher zones of inhibition for all the isolates, including Methicillin-resistant S. aureus, E. coli ESBL, meropenem-resistant E. coli, than the rest of the extracts, with zones of inhibition ranging from 20.0 mm to 32.5 mm. Ethyl acetate seed extract also inhibited all the isolates except Meropenem-resistant E. coli. Likewise, ethyl acetate leaf extract inhibited all except the E. coli isolates and had significantly higher zones inhibition for almost all the isolates compared to the ethyl acetate seed extract. However, aqueous seed extract showed the lowest minimum inhibitory concentration against all bacteria strains, ranging from 50 mg/ml to 200 mg/ml. Conclusions The data indicates that aqueous and ethyl acetate extracts of M. oleifera, particularly aqueous seed extract, have the potential of capturing inhibitors against drug-resistant and clinical isolates of S. aureus, P. aeruginosa and E. coli.